Pengaruh Kualitas Layanan, Motivasi Kerja Dan Inovasi Kerja Terhadap Kepuasan Nasabah KUR MIKRO di BRI Unit Mejoyo Surabaya - Ketut Witara; Dodit Cahyo Nugroho, SE., MM.; Wiranda Yurdan Adi Putra (Economics and Digital Business Review, 2023)
This research aims to determine the level of customer satisfaction for Micro KUR at Bank BRI Unit Mejoyo Surabaya. In this case the level of satisfaction is measured using service quality indicators including Tangible, Reliability, Responsiveness, Assurance, and Empathy, Work Motivation and Innovation. The method used in this research is quantitative. With the aim of realizing better services by helping MSME businesses develop by channeling Micro KUR loans. The test equipment used is the reliability test and validity test, the results of the data test show valid and reliable data. The results of the research are Service Quality (X1) and Work Motivation (X2) simultaneously have a significant and partially significant effect on Work Innovation (Z). Service Quality (X1) and Work Motivation (X2) simultaneously have a significant effect and partially have no significant effect on Customer Satisfaction (Y). Job Innovation (Z) simultaneously and partially has a significant effect on Customer Satisfaction (Y). Service Quality (X1) through Work Innovation (Z) simultaneously, partially, and Sobel test has a significant effect on Customer Satisfaction (Y). Work Motivation (X2) through Work Innovation (Z) simultaneously has a significant effect, while partially and sobel test has no significant effect on Customer Satisfaction (Y).